2010
DOI: 10.1021/nn101990a
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Polymer Architecture Mediates Switching of Complement Activation Pathways at the Nanosphere−Serum Interface: Implications for Stealth Nanoparticle Engineering

Abstract: Nanoparticles with surface projected polyethyleneoxide (PEO) chains in "mushroom؊brush" and "brush" configurations display stealth properties in systemic circulation and have numerous applications in sitespecific targeting for controlled drug delivery and release as well as diagnostic imaging. We report on the "structure؊activity" relationship pertaining to surface-immobilized PEO of various configurations on model nanoparticles, and the initiation of complement cascade, which is the most ancient component of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
239
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(253 citation statements)
references
References 39 publications
(113 reference statements)
12
239
2
Order By: Relevance
“…Like, PEG, PEO forms a mushroom-or brush-like configuration on the surface of NPs. Unlike PEG, however, PEO may activate the C1q-dependent complement pathway in its mushroom-like configuration, whereas the brush-like configuration can trigger the lectin-specific complement cascade [44]. Interestingly, although NP coatings may prolong NP serum half-life, cells of the MPS still appear to be involved in the primary clearance mechanism for intravenously infused NPs [43].…”
Section: Factors Associated With Particle Opsonizationmentioning
confidence: 99%
“…Like, PEG, PEO forms a mushroom-or brush-like configuration on the surface of NPs. Unlike PEG, however, PEO may activate the C1q-dependent complement pathway in its mushroom-like configuration, whereas the brush-like configuration can trigger the lectin-specific complement cascade [44]. Interestingly, although NP coatings may prolong NP serum half-life, cells of the MPS still appear to be involved in the primary clearance mechanism for intravenously infused NPs [43].…”
Section: Factors Associated With Particle Opsonizationmentioning
confidence: 99%
“…While surface modifications (such as PEGylation 39 ) reduce the binding of additional biomolecules, some association of biomolecules may still occur 35,40 . Their presence may lead to more subtle and poorly understood biological consequences, issues possibly related to current struggles in achieving efficient targeting of nanomedicines in vivo.…”
mentioning
confidence: 99%
“…The possibility of tuning the adsorption of proteins is also described here. This might have consequences in determining the final fate of NPs in organisms since important processes such as cell uptake [48] or activation of the complement systems are known to be influenced by the adsorption of proteins [11]. Last but not least, a properly designed mixed layer gives the opportunity to tune both functionality and stability of the NPs.…”
Section: Discussionmentioning
confidence: 99%
“…This has strong consequences on the design of NPs for medicine. For example, a different degree and type of complement activation, which ultimately depends on the recognition of the conjugates by specific proteins, was directly correlated with the conformation of the PEO monolayer on polymeric NPs in a recent work [11]. Briefly, Hamad et al showed that the complement activation was dramatically reduced for the nanospheres which have PEO chains in the brush conformation.…”
Section: Mixed Monolayer Interaction With Protein Coronamentioning
confidence: 99%
See 1 more Smart Citation